A Rare Presentation of Herlyn Werner Wunderlich Disease in Young Female - Zampieri, Nicola (Archives of Clinical and Medical Case Reports, 2020)
Background: Herlyn-Werner-Wunderlich syndrome is a rare urogenital anomaly consisted of renal agenesia, uterovaginal duplication and ipsilateral blind hemivagina. Usually it presents some months after menarche with pelvic pain, acute abdomen, intermenstrual bleeding. Case report: A 13 year premenarchal female was transferred to our unit for acute abdomen and MR findings of left renal agenesis, blind hemivagina distended by ematic material, complete uterus duplication , dilated tuba and left ovarian mass with torsion. A diagnostic laparoscopy was performed during which detorsion of the ovarian tubal complex was performed with resection of ovarian cyst. Summery and Conclusion: This is a rare syndrome and ovarian torsion is never reported as complication